Strategi Pengelolaan Sumber Daya Manusia Terhadap Pengembangan Badan Usaha Milik Desa - Meida Rachmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Village development has the aim of improving human welfare and overcoming poverty through efforts to provide and fulfill basic needs, build village infrastructure, develop local economic potential and utilize natural resources and friendships on an ongoing basis. One of the efforts that will be implemented is as a means to develop villages, namely the existence of BUMDes. BUMDes was formed to manage village potential where the capital comes from the village's wealth. This paper uses qualitative methods with the aim of analyzing strategies that can be implemented in managing human resources for the development of BUMDes. This paper concludes that HR management strategies not only contribute to village economic growth but also to maintaining the environment which is the basis of community life in rural areas. The strategy that can be used to manage human resources in order to create development of village-owned enterprises is to increase HR competency through training, through knowledge, through innovation, through experience and through the education process.